2016
DOI: 10.1186/s13287-016-0409-x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and efficient generation of neural progenitors from adult bone marrow stromal cells by hypoxic preconditioning

Abstract: BackgroundBone marrow stromal cells (BMSCs) are attractive as a source of neural progenitors for ex vivo generation of neurons and glia. Limited numbers of this subpopulation, however, hinder translation into autologous cell-based therapy. Here, we demonstrate rapid and efficient conditioning with hypoxia to enrich for these neural progenitor cells prior to further expansion in neurosphere culture.MethodAdherent cultures of BMSCs (rat/human) were subjected to 1 % oxygen for 24 h and then subcultured as neurosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 29 publications
0
27
0
Order By: Relevance
“…However, hypoxia did not alter the ability of neurospheres to form neuron and glia precursors. In addition, Schwann celllike cells obtained from hypoxia-preconditioned BMSCs expressed S100b /p75 and the ability for myelination in vitro 44 .…”
Section: Discussionmentioning
confidence: 97%
“…However, hypoxia did not alter the ability of neurospheres to form neuron and glia precursors. In addition, Schwann celllike cells obtained from hypoxia-preconditioned BMSCs expressed S100b /p75 and the ability for myelination in vitro 44 .…”
Section: Discussionmentioning
confidence: 97%
“…In another study that conducted with KL Mung and colleagues, demonstrated that bone marrow mesenchymal stem cells express GFAP under hypoxia condition [30]. These proteins produce a network for cell protection and strength.…”
Section: Discussionmentioning
confidence: 96%
“…Using mesenchymal stromal/stem cells (MSCs) as a source for neurogenesis has been tested rigorously in the hope that non‐NSCs may be used as a cell source for neural regeneration. However, the results have been controversial and inconsistent (Aanismaa, Hautala, Vuorinen, Miettinen, & Narkilahti, ; Arthur, Rychkov, Shi, Koblar, & Gronthos, ; Chen et al, ; Deng, Petersen, Steindler, Jorgensen, & Laywell, ; Gervois et al, ; Jung, Kim, Moon, Hong, & Hyun, ; Mung et al, ; Pittenger et al, ; Shiota et al, ; Tondreau et al, ; Wehner et al, ). Many reports attempted to define NSC properties of MSCs only by detecting gene expression but not examining or demonstrating the functional electrophysiology that is the critical characteristic of neurons.…”
Section: Introductionmentioning
confidence: 99%